The Nye Canyon Paleo Site: an Upper Montane Mixed Fluted Point, Clovis Blade, and Western Stemmed Tradition Assemblage in Western Nevada. (3rd April 2022) - Rhode, David; Smith, Geoffrey M.; Dillingham, Eric; Kingrey, Haden U.; George, Nicole D.
ABSTRACT: The place of the Clovis techno-complex in Great Basin culture history remains enigmatic, both in relation to the Western Stemmed Tradition – the dominant Paleoindian artifact complex in the Intermountain West – and to the range of late Pleistocene/early Holocene habitats that people employing Clovis toolkits utilized. Here we describe the Nye Canyon Paleo Site (26Ly930), located in the Pine Grove Hills in western Nevada. The Nye Canyon Paleo Site stands alone in the Great Basin because it contains both fluted points and Clovis-style blades alongside Western Stemmed Tradition points and other tools, sits at a relatively high elevation, and potentially contains buried cultural deposits. Recent test excavations failed to locate an intact buried Paleoindian component, but the Nye Canyon Paleo Site nevertheless demonstrates the use of Clovis and Western Stemmed technology at a single upper montane locality in the western Great Basin and highlights regional Paleoindian upper montane land use.